Research on the development and management of clinical pathways Ⅱ: information management of clinical pathways - LIN Kewen; LOU Jia'ao; PENG Shuzhen; YI Ye; JIN Yinghui; FENG Jiajia; ZHANG Pan; XIONG Hao; HE Qian; WANG Xinghuan; LIN Likai (Yixue xinzhi zazhi)
Clinical pathway informatization is the inevitable trend of clinical pathway development. Based on the hospital management information system, it can realize the clinical pathway information management and build the knowledge base of clinical path decision-making and treatment. It can further support the adaptive dynamic adjustment of clinical pathway. Informatization of clinical pathway is the core of clinical pathway information management. This article elaborates the construction basis of clinical pathway information management and the construction of clinical pathway knowledge base, so as to provide reference for the development and management of clinical pathway from the perspective of information management.